2012
DOI: 10.1111/j.1440-1797.2012.01637.x
|View full text |Cite
|
Sign up to set email alerts
|

Real‐time ultrasound guided placement of temporary internal jugular vein catheters: Assessment of technical success and complication rates in nephrology practice

Abstract: Cannulation of IJV under real-time ultrasound guidance is very safe with high technical success rates. Nephrologists can use this technique with ease and with minimal complications in normal- and high-risk patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 16 publications
0
8
0
3
Order By: Relevance
“…99 A study of renal failure patients found high success rates and low complication rates in the patients with a history of multiple previous catheterizations, poor compliance, skeletal deformities, previous failed cannulations, morbid obesity, and disorders of hemostasis. 100 A prospective observational study of 200 ultrasound-guided CVC insertions for apheresis showed a 100% success rate with a 92% first-pass success rate. 101 The use of real-time ultrasound guidance for IJV CVC insertion has been shown to be cost effective by reducing procedure-related mechanical complications and improving procedural success rates.…”
Section: We Recommend That Providers Should Use Real-time Ultrasound mentioning
confidence: 99%
“…99 A study of renal failure patients found high success rates and low complication rates in the patients with a history of multiple previous catheterizations, poor compliance, skeletal deformities, previous failed cannulations, morbid obesity, and disorders of hemostasis. 100 A prospective observational study of 200 ultrasound-guided CVC insertions for apheresis showed a 100% success rate with a 92% first-pass success rate. 101 The use of real-time ultrasound guidance for IJV CVC insertion has been shown to be cost effective by reducing procedure-related mechanical complications and improving procedural success rates.…”
Section: We Recommend That Providers Should Use Real-time Ultrasound mentioning
confidence: 99%
“…Success rates rise and complication levels also decrease in patients with CRF when catheter placement is performed using USG. Studies using USG in real time in hemodialysis catheter insertion have recorded first entry success rates of 56-85% and average number of needle puncture ranged between 1.17 and 1.75 [2,8]. USG has been shown to be superior to the anatomical landmark technique in these studies.…”
Section: Discussionmentioning
confidence: 81%
“…Several studies to date have compared the effectiveness of different forms of USGguided catheter insertion for hemodialysis in patients with chronic renal failure (CRF) [6][7][8]. This study was planned to determine the difference between for pre-catheterization vascular mapping and real time use of USG Abstract Aim: Ultrasound (USG)-guided hemodialysis catheter placement is known to be superior to and more reliable than catheter insertion guided by anatomical landmarks.…”
Section: Introductionmentioning
confidence: 99%
“…In MO, central venous access could be particularly difficult, although this obstacle has been partly solved by echography [28,29]. Furthermore, the invasiveness of PAC TD is not justified with improved outcomes [10,11], and it has significant direct patient risk such as malignant arrhythmias [30,31], pulmonary artery rupture [32], and death [33].…”
Section: Discussionmentioning
confidence: 99%